The runaway princess - Dickins, Rosie (Usborne Publishing Ltd London, 2013)
A princess runs away to avoid marriage, taking three of her favourite gowns with her. She works hard, herding geese in a tatty donkeyskin cloak, but when she thinks no one is looking, she tries on one of her beautiful gowns. She is spotted by a prince who falls in love with her at first sight, but she runs away. How will he find her? And what will he think when he finds out that she's just a goose girl? A variation of the Cinderella story, this version is based on Donkeyskin, a 300-year-old story by the French author, Charles Perrault. Part of the Usborne Reading Programme, which includes over 250 titles across seven levels - all developed in conjunction with reading experts at Roehampton University.